Determinants of the Success of Development in Kesiman Kertalangu Village - Ida Ayu Paramitha Wulandari; Anak Agung Ketut Ayuningsasi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the factors influencing the success of development in Kesiman Kertalangu Village. The factors examined include village institution revenue, labor force, investment, and community participation. Development, in general, can be defined as efforts to enhance the productivity of resources owned by a region, such as natural resources, human resources, and financial resources. However, development in Kesiman Kertalangu Village faces challenges, namely changes in economic structure and land use conversion, which impact the regional development. This research employs a quantitative approach with multiple linear regression analysis to examine the relationship between independent variables (village institution revenue, labor force, investment, and community participation) and the dependent variable (village development success). The data used are secondary time series data collected annually from 1995 to 2024. Data were gathered through literature review by obtaining information from credible official sources, including government agencies, the Central Bureau of Statistics, and the Kesiman Kertalangu Village Office. Data analysis was conducted using Eviews 12 software. The results indicate that village institution revenue, labor force, investment, and community participation simultaneously have a significant effect on the success of development in Kesiman Kertalangu Village. Moreover, labor force, investment, and community participation have a positive and significant partial effect on development success, while village institution revenue has a positive but not significant partial effect. The findings also reveal that investment is the most dominant factor influencing the success of development in Kesiman Kertalangu Village. Theoretically, the finding that investment has a dominant influence on the success of Kesiman Kertalangu Village development strengthens the Solow growth model, Robert Chambers' participatory theory, and Amartya Sen's capacity building concept. Practically, the research results provide strategic direction for village governments and stakeholders in designing participation- based development policies, increasing fiscal capacity, and empowering local workers.